PENGARUH TEKNIK DEFOLIASI DAN PEMBERIAN DOSIS PUPUK NPK 16:16:16 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata Strut.) - Yustika, Aninda; Budi, Setyo; Nur Lailiyah, Wiharyanti (Journal of Agro Plantation (JAP), 2023)
Sweet corn is the second source of carbohydrates after rice. The purpose of this study was to determine the effect of the Defoliation technique and variations in NPK 16:16:16 doses so as to increase the growth and yield of sweet corn plants. The research was conducted at the Hollywood Experimental Field, Klangonan Village. The time for conducting the research was from August to October 2022. The tools needed during the research included: sickle, machete, hoe, tape measure, ruler, raffia rope, bucket, cellphone, brix and stationery. While the materials needed include: sweet corn seeds, NPK 16:16:16 fertilizer. Two-factor Randomized Block Design (RBD), namely the defoliation technique on sweet corn plants and the application of Pearl NPK fertilizer. The first factor is the defoliation technique (D) and the second factor is Pearl NPK fertilization (P) resulting in 3 levels. Each treatment was repeated 3 times to get 27 experimental units. If the results are significantly different (F Count > F table) then the analysis is continued by using the BNT test at the 5% level. From the results of the study there were significant differences in the application of the defoliation technique and the application of NPK 16:16:16 fertilizer to sweet corn.